2023
DOI: 10.1021/acs.est.3c00777
|View full text |Cite
|
Sign up to set email alerts
|

Peroxymonosulfate Activation by Fe(III)–Picolinate Complexes for Efficient Water Treatment at Circumneutral pH: Fe(III)/Fe(IV) Cycle and Generation of Oxyl Radicals

Abstract: Improving the reactivity of Fe(III) for activating peroxymonosulfate (PMS) at circumneutral pH is critical to propel the iron-activated PMS processes toward practical wastewater treatment but is yet challenging. Here we employed the complexes of Fe(III) with the biodegradable picolinic acid (PICA) to activate PMS for degradation of selected chlorinated phenols, antibiotics, pharmaceuticals, herbicides, and industrial compounds at pH 4.0− 6.0. The Fe III −PICA complexes greatly outperformed the ligand-free Fe(I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(4 citation statements)
references
References 54 publications
1
3
0
Order By: Relevance
“…This result suggests that structural Fe­(II), rather than aqueous Fe 2+ dominated the formation of PMSO 2 [i.e., Fe­(IV)]. Many previous studies have demonstrated the formation of aqueous Fe­(IV) during the oxidation of Fe 2+ in advanced oxidation processes. Our results extended the generation of Fe­(IV) from homogeneous Fe 2+ systems to structural Fe­(II) associated with clay minerals.…”
Section: Resultssupporting
confidence: 67%
“…This result suggests that structural Fe­(II), rather than aqueous Fe 2+ dominated the formation of PMSO 2 [i.e., Fe­(IV)]. Many previous studies have demonstrated the formation of aqueous Fe­(IV) during the oxidation of Fe 2+ in advanced oxidation processes. Our results extended the generation of Fe­(IV) from homogeneous Fe 2+ systems to structural Fe­(II) associated with clay minerals.…”
Section: Resultssupporting
confidence: 67%
“…Furthermore, picolinic acid derivatives have been used for (noble)metal-catalysed reactions in the fields of water oxidation, 25 photochemistry, 26,27 and others. 28–32…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, diethylenetriaminepentaacetic acid (DTPA) and ethylenediaminetetraacetic acid (EDTA) are nonbiodegradable, and NTA is carcinogenic. The widely used 2-pyridinecarboxylic acid (PICA) will also increase the organic load and nitrogen content, which is unfavorable for wastewater treatment . Moreover, EDDS has been shown to improve the efficiency of Fenton and Fenton-like oxidation and is gradually being extensively studied. , Therefore, EDDS was considered as a candidate to enhance the catalytic efficiency of the Mn­(II)/PAA system.…”
Section: Introductionmentioning
confidence: 99%